HIV Nurse Navigation: Charting the Course to Improve Engagement in Care and HIV Virologic Suppression. (November 2017) - Hemmy Asamsama, Octaviana; Squires, Leah; Tessema, Alpha; Rae, Ephrem; Hall, Karen; Williams, Rush; Benator, Debra
This study represents one of the few exploring the effectiveness of an integrated HIV nurse navigation program on engagement and virologic outcomes. A navigator provided individualized care management (eg, pillbox renewals), intensive outreach, and collaboration with existing support systems (eg, families, community programs). Clinical data from the Veterans Affairs (VA) Medical Center site of a longitudinal, observational study of HIV in the District of Columbia (DC) cohort were used for comparison (N = 706). Navigation patients (n = 84) were less likely to have permanent housing, and more likely to be disabled, have detectable viral load, comorbid depressive, and substance use disorders. Navigation patients showed improvements in clinic visits (doubled), rate of medication renewal (40.91% to 80.61%), CD4 count and CD4%, and viral rates of Veterans with <200 copies/mL increased from 47.6% to 69.0% after one year. Integration of nurse navigation into a HIV primary care setting shows promise in improving engagement and virologic suppression in a high-risk population.